Rozwój bezpośredniej sprzedaży produktów rolniczych w województwie podkarpackim - Dziedzic, Sylwia; Woźniak, Leszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article presents results of a research on direct sales of agricultural products. The research was conducted in 2005 in Subcarpathia Voivodeship. There was selected a group of 8.9% respondents who find direct sales as a significant source of farm income. In the future, all educational and advisory efforts should be directed first towards this group to enhance its potential. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 310-314